2009
DOI: 10.5539/ijbm.v3n11p93
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Work Life Conflict, Stress and Turnover Intentions among Marketing Executives in Pakistan

Abstract: This study examines the antecedents of turnover intentions among marketing executives in Pakistan. Relationship between stress and work life conflict with turnover intentions was examined. The research data was collected from 248 marketing executives working in different organizations across Pakistan. The results suggest that of work life conflict and stress have a significant positive relationship with turnover intentions. Recommendations and strategies are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 68 publications
(57 reference statements)
5
32
0
12
Order By: Relevance
“…This hypothesis is rejected after applying statistical test which means that work life conflict has no effect on doctors' intention to leave the hospital. Noor and Maad, (2008) revealed that work life conflict and stress have a significant positive relationship with turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is rejected after applying statistical test which means that work life conflict has no effect on doctors' intention to leave the hospital. Noor and Maad, (2008) revealed that work life conflict and stress have a significant positive relationship with turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Noor and Maad (2008) examined the relationship between stress, one of the causes of burnout, and work life conflict with turnover intentions, have revealed that work life conflict and stress have a significant positive relationship with turnover intentions. Ronen and Pines, (2008) investigated the gender differences in burnout, style of coping and the availability of peer support among high-tech engineers and have revealed that there was a significant gender difference in burnout, with women engineers reporting higher levels of burnout than men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees should try to understand the common causes of employee conflicts so that a solution is found before the issues become unmanageable and entails into an irreparable loss. There has also been a significant rise in the communication conflicts among employees at the workplaces in Pakistan (Mansoor, Fida, Nasir, & Ahmad, 2011;Nasir & Bashir, 2012;Noor & Maad, 2009). The irony of the fact is that these conflicts are widely hidden and avoided instead of resolving them effectively (Chaudhry, 2011;Farooqi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[12] At the organizational level, stress due to work is associated with the consequences such as complaints, grievances, staff turnover, decrease in motivation and satisfaction, fatigue resulting from long hours of work or shift work, and occupational violence, which have negative impacts on product and service quality thereby affecting the economy as well as the reputation of the organization. [2,13] A study by Noor [14] among marketing executives in Pakistan found workplace stress as an important predictor of staff turnover in organizations. Moreover, a recent report from the ILO mentioned that 40% of global employee turnover was attributed to stressors at work.…”
Section: Extent Of the Problemmentioning
confidence: 99%